DISSOCIATIVE IDENTITY DISORDER OF THE MAIN CHARACTER IN THE SECRET WINDOW MOVIE - Sudding, Muhammad Fahri Jaya; Sudding Sally, Fauzan Hari (Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
The objectives of the research were to find out the main cause of Dissociative Identity Disorder of the main character in a movie called The Secret Window, the symptoms of Dissociative Identity Disorder of the main character, and the effects of Dissociative Identity Disorder on the main character. The data were taken from the main character in the Secret Window movie, characterization, dialogue, plot, and the movie itself. The method used by the researchers in this research was the descriptive qualitative method. The results of this research showed that: 1) the cause of the Dissociative Identity Disorder of the main character, Morton Rainey, was when he found his wife was cheating on him, 2) there were two symptoms that appeared in Morton Rainey’s disorder: heard voices and amnesia, 3) the effects of Dissociative Identity Disorder on Morton Rainey was he murdered his wife, Amy Morton and Amy’s affair, Ted Milner.